1995
DOI: 10.1016/0550-3213(94)00448-n
|View full text |Cite
|
Sign up to set email alerts
|

Integrable vertex and loop models on the square lattice with open boundaries via reflection matrices

Abstract: The procedure for obtaining integrable vertex models via reflection matrices on the square lattice with open boundaries is reviewed and explicitly carried out for a number of two-and three-state vertex models. These models include the six-vertex model, the 15-vertex A(1) 2 model and the 19-vertex models of Izergin-Korepin and Zamolodchikov-Fateev. In each case the eigenspectra is determined by application of either the algebraic or the analytic Bethe ansatz with inhomogeneities. With suitable choices of reflec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 44 publications
(112 reference statements)
3
103
0
Order By: Relevance
“…where In particular, we found that the known diagonal reflection matrices for the Izergin-Korepin model [24] lead to two integrable sets of boundary weights which preserve the O(n) symmetry [22,25]. For each case t b = tb = 2 cos λ.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…where In particular, we found that the known diagonal reflection matrices for the Izergin-Korepin model [24] lead to two integrable sets of boundary weights which preserve the O(n) symmetry [22,25]. For each case t b = tb = 2 cos λ.…”
Section: Introductionmentioning
confidence: 99%
“…The two integrable sets of boundary weights are [22] (A) t s = sin 2λ sin λ and (B) t s = cos 2λ cos λ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Email addresses: rsvieira@df.ufscar.br (R. S. Vieira), dals@df.ufscar.br (A. Lima Santos) had been diagonalized before, through the fusion procedure [26], in [27] and, with inhomogeneities, in [28]) and coordinate Bethe Ansatz of the IKvm was obtained in [29]; the algebraic Bethe Ansatz for the ZFvm and IKvm were derived respectively in [25] and [30]. Considering now nonperiodic boundary conditions, the diagonal K-matrices for the ZFvm were first derived in [31] and the general Kmatrices were deduced in [32] and [33]; for the IKvm, the diagonal K-matrices were found in [34] and the general K-matrices were derived in [33] and [35]; besides, the coordinate Bethe Ansätze for both models were presented in [36], while their algebraic versions were performed in [37] (although the ZFvm had been considered before in [31] with the help of the fusion procedure [26]).…”
Section: (Although Its Hamiltonianmentioning
confidence: 99%